2021
DOI: 10.1016/j.annonc.2021.08.964
|View full text |Cite
|
Sign up to set email alerts
|

443P EMERGE: A phase II trial assessing the efficacy of domatinostat plus avelumab in patients with previously treated advanced mismatch repair proficient oesophagogastric and colorectal cancers – phase IIA dose finding

Abstract: Background: The prevalence of BRAF V600E in colorectal cancer (CRC) was about 10%. Despite recent therapeutic advances, BRAF V600E mutant CRC is still a challenge with a low response rate and suboptimal survival. Here we reported the safety and preliminary anti-tumor activity of vemurafenib and cetuximab in combination with FOLFIRI for BRAF V600E-mutated advanced CRC patients.Methods: In this single-arm, single-center trial, we are currently in enrollment of patients with BRAF V600E-mutated, RAS-wild type adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Domatinostat, currently in clinical development in both in hematological and solid malignancies, has shown a good safety profile also in combination treatments [ 43 46 ]. In this regard, in our study we demonstrated a selective anti-tumour effect of domatinostat on tumor cells and a good tolerability of treatment in combination with chemotherapy in mice preclinical model.…”
Section: Discussionmentioning
confidence: 99%
“…Domatinostat, currently in clinical development in both in hematological and solid malignancies, has shown a good safety profile also in combination treatments [ 43 46 ]. In this regard, in our study we demonstrated a selective anti-tumour effect of domatinostat on tumor cells and a good tolerability of treatment in combination with chemotherapy in mice preclinical model.…”
Section: Discussionmentioning
confidence: 99%